Literature Review: Use of Smartphones in Education for HIV/AIDS Patients - Fatimatuzahro, Fatimatuzahro; Widjanarko, Bagoes; Shaluhiyah, Zahroh (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
HIV/AIDS is an infectious disease and a cause of death in Indonesia. This disease requires medication adherence. Education plays an important role in the success of treatment adherence of HIV/ADIS patients. This study aims to analyze the use of smartphones in education on HIV/AIDS. The research design is a literature review using a systematic review by collecting research articles on the use of smartphones in education for HIV/AIDS patients. There are 10 research articles, with a period of 2017-2022. The results of the analysis of the articles show that the use of smartphone-based applications plays an important role in increasing the compliance of HIV/AIDS patients undergoing ARV treatment. Abstrak: HIV/AIDS merupakan penyakit yang menular dan menjadi penyebab kematian di Indonesia. Penyakit ini membutuhkan kepatuhan dalam pengobatan. Edukasi memegang peran penting dalam keberhasilan kepatuhan pengobatan pasien HIV/ADIS.  Penelitian ini bertujuan untuk menganalisis penggunaan smartphone dalam edukasi pada HIV/AIDS. Desain penelitian adalah literature review menggunakan systematic review dengan mengumpulkan artikel-artikel penelitian mengenai penggunaan smartphone dalam edukasi pada pasien HIV/AIDS. Artikel penelitian sebanyak 10 artikel dengan rentang waktu 2017-2022. Hasil analisis terhadap artikel-artikel diketahui bahwa penggunaan aplikasi berbasis smartphone berperan penting dalam meningkatkan kepatuhan pasien HIV/AIDS menjalani pengobatan ARV. Pasien HIV/AIDS yang menggunakan aplikasi berbasis smartphone menunjukkan peningkatan kepatuhan pengobatan ARV.